Analysis of the Strength Thorn Pandan Leaves Fiber Composite: Woven Vs Random Fibers - Lani; Fuazen; Eko Julianto; Muhammad Iwan; Eko Sarwono; Gunarto (Universitas Muhammadiyah Sidoarjo, 2024)
This study focuses on assessing a composite material that uses pearly leaf reinforcement and a polyester resin matrix as a construction material for energy-efficient automobile bodies. The traction strength test and impact resistance test of thorn panda leaf fiber are conducted to evaluate the difference in fiber direction, namely induced and random. This discovery is anticipated to be advantageous for the development of energy-efficient automobile bodywork. The highest traction force recorded is 2199.63 MPa in the random fiber direction, whereas the lowest traction strength is 2077.43 MPa in the fiber direction. The pulling force increases when the direction of the fiber aligns with the pulling manner, resulting in more force. The impact's greatest absorbent energy strength is 0.623 j in the direction of the fiber, while the least absorbent energy strength is 0.595 j in the direction of the random fiber.